Socialization of Village Development by Integrating Agriculture, Education, and Tourism Businesses in Mlese Village, Klaten District - ., Kartinah; Prasetyowati, Dina; Umiyati, Rini; Junaedi, Sony (KnE Social Sciences, 2024)
Mlese village has a large area of agricultural land that has a lot of potential that can be developed. Large and fertile agricultural land has the potential to become a national food barn to support food self-sufficiency programs. Realizing the value of the potential of Mlese village, both according to the aspects of agriculture, economy, and food security and seeing the tourism potential that has not been optimized, it encourages the service team from PGRI Semarang University together with the village community to develop a tourism village which will be called the AGROEDUTOURISM Tourism Village. This activity is a part of the community service program of the PGRI Semarang University service team to assist Mlese villagers to realize a tourist village with three fields developed, namely integrated agriculture, education, and tourism. The method used in this community service activity is through the workshop, training, demonstration, and mentoring methods. Some of the assistance through workshops and trainings that have been carried out, obtained the following results: The program socialization and entrepreneurship motivation workshop of 20 participants were attended by the heads and secretaries of Farmer Groups, Youth Farmer Groups, Pokdarwis Groups, and Women Farmer Groups (WFG) in Mlese village. After the chairpersons and secretaries obtained the workshop materials, they were expected to pass them on to all members. As many as 85% of the participants who attended the integrated farming training were already skilled in demonstrating and practicing the knowledge gained from the resource persons. One of the physical developments made at the AGROEDUTOURISM location is the Green House and has reached 85%. For the education sector, because one of the physical developments made at the AGROEDUTOURISM site is the Green House, and in the village there is a public elementary school whose curriculum includes out-of-class activities (Outing Class). The establishment of the Green House is not only a place for the Community’s integrated agricultural hatchery, but also an Outing Class destination for students at the elementary school. Keywords: village tourism, agroedutourism, community service